Antioxidant Activity of Extracts from Simao Pine (Pinus kesiya var. langbianensis) Needles - Kan, Xurundong; Liu, Yaning; Qiu, Li (International Journal of Public Health and Medical Research, 2026)
Simao pine is a dominant native tree species in Puer, Yunnan, China, with abundant underutilized pine needle resources. This study optimized the ultrasonic-assisted extraction of total flavonoids from Simao pine needles, and evaluated the in vitro antioxidant activity of the extracts. Single-factor experiments and orthogonal test showed that the optimal extraction conditions were solid-liquid ratio 1:20, extraction temperature 80℃, and extraction time 40 min, with a maximum total flavonoid yield of 6.86%. The total phenolic content of the extract was 10.97 μg per mg of dry extract. Antioxidant assays confirmed that the extract had a DPPH radical scavenging rate over 80% at 0.6–0.8 mg/mL, and a maximum hydroxyl radical (•OH) scavenging rate of 72.29% at 0.8 mg/mL. The reducing power of the extract was significantly higher than that of vitamin C (Vc) and vitamin E (Ve) at 0.6–1.0 mg/mL. This study provides a theoretical basis for the development of Simao pine needles as a natural antioxidant resource.